2012
DOI: 10.1016/j.jtcvs.2012.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of gastroesophageal reflux disease: A review

Abstract: Gastroesophageal reflux disease is the most common esophageal disorder encountered in the United States. Gastroesophageal reflux disease symptoms are associated with a negative quality of life and increased healthcare costs and therefore require an effective management strategy. Although proton pump inhibitors remain the primary treatment of gastroesophageal reflux disease, they do not cure the disorder and can leave patients with persistent symptoms despite treatment. Moreover, patients are still at risk of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Narsule et al 7 reviewed the development of endoscopic treatment of GERD and summarized the results from more than 20 surgical studies using the EsophyX system in 2012. The patient follow-up in these studies ranged from 2 to 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Narsule et al 7 reviewed the development of endoscopic treatment of GERD and summarized the results from more than 20 surgical studies using the EsophyX system in 2012. The patient follow-up in these studies ranged from 2 to 24 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported serious immediate complications and procedure failures. 7 , 9 , 10 A prospective multicenter trial conducted at seven clinical centers enrolled 86 patients in 2006. 5 The inclusion criterion required chronic GERD treated with PPIs; the exclusion criterion was an irreducible hiatal hernia >2 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients with persistent reflux that fails drug therapy, may be referred for evaluation of surgical management, for example, patients with diagnosed hiatus hernia may benefit from fundoplication. Antireflux surgery (including various forms of fundoplication and devices such as EsophyX and LINX) for GORD presents alternatives and adjuncts to long-term antireflux medication, for those with refractory symptoms 27. There are stringent criteria for such surgery, outside the scope of this paper.…”
Section: Managementmentioning
confidence: 99%
“…Endoscopic techniques, such as EsophyX, may be performed by interventional upper GI physicians and are minimally invasive. However, laparoscopic surgery under upper GI surgeons (fundoplication, LINX and others) are thought to have better long-term effectiveness 6 27. These would be used following proof of classic GORD through both OGD and 24 hours pH-impedance testing, but their place in assisting extraoesophageal symptoms alone, as with PPIs, is presently controversial.…”
Section: Managementmentioning
confidence: 99%